Addition of seminal plasma proteins effecting the in vitro kinetic properties of canine spermatozoa - Tsvetkov, Tsvetan; Petrova, Nadya; Daskalova, Denica (Veterinarni medicina, 2022)
The objective of this study is to evaluate the changes in the motility and kinetic patterns of canine spermatozoa, capacitated and decapacitated, after the addition of seminal plasma protein fractions with different molecular weight. It has been proposed that proteins in seminal plasma support the survival of the spermatozoa and exert a dual effect: capacitation and decapacitation. The seminal plasma from fresh ejaculates was subjected to chromatographic separation and four protein fractions were obtained. Computer-assisted sperm analysis was used to determine the sperm subpopulations with specific motion and kinetic characteristics after incubation with each of the four protein fractions. Two-dimensional electrophoresis of the fractions that exhibit a significant effect on the capacitation and decapacitation was performed. By sperm class analyser, capacitation changes were observed in the sperm subpopulation with a high curvilinear velocity and amplitude of lateral head displacement incubated with the seminal plasma protein fraction with a high molecular weight, which was also reflected in the decreased linearity, straightness, and progressive motility. The sperm subpopulation incubated with the seminal plasma protein fraction with a low molecular weight seemed to undergo a process of decapacitation (decreasing of the curvilinear velocity, increasing of the linearity, straightness and showing progressive motility). Despite their ample panorama of actions, the role of seminal plasma proteins regarding capacitation and decapacitation is still undetermined.
Keywords: decapacitation; capacitation; motility; kinetics